Developing lasts with removable toe parts for customized footwear - Liliia Chertenko; Tatjana Spahiu; Tymofii Lypskyi; Henrique Almeida; Olexander Bondar (Communications in Development and Assembling of Textile Products)
The scope of this work is to develop lasts with a removable toe part as one of the ways to optimize the range of lasts while maintaining a high level of conformity of the last shape to the individual measurements of the feet of customers. For this purpose, the sectional plane separating the toe part of different shapes and styles from the main back part, which corresponds to the measurements of the foot, is determined by the area of minimal deviations of the parameters of feet shapes and lasts in different 3D models. The interchange of toe parts between different lasts is carried out under the condition of a small difference between their major parameters when it is possible to perform the averaging of the shapes and dimensions of the sectional plane of different lasts without reducing the ergonomics of their shapes. The segmentation plane divides the last body in such a way that the removable toe parts can be attached to the main back parts of the lasts of different styles and forms, as well as with different heel heights, which increases the use efficiency of the replaceable elements